1994
DOI: 10.1038/sc.1994.131
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between physical strain during standardised ADL tasks and physical capacity in men with spinal cord injuries

Abstract: To describe physical strain during activities of daily living (ADL) , 44 men with spinal cord injuries (C4-L5) performed a set of standardised tasks. The physical strain was defined as the highest heart rate response expressed as a percentage of the individual heart rate reserve (% HRR). The physical strain averaged over the subjects who performed all tasks ( n = 24) was (mean ± SD): 20.2 ± 7.2 %HRR (washing hands), 20.4 ± 7.3 %HRR (passing a side-hung door), 28.8 ± 10.8 %HRR (transfer to a toilet), 31.2 ± 13.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
53
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 18 publications
3
53
0
1
Order By: Relevance
“…There is also the absence of sufficient recovery time: subjects must perform lifts during the day and propel themselves. Tasks like making a transfer are performed around 15 times a day, 1 and, as shown by Janssen et al, 32 a physical strain of 60% of the heart rate reserve occurs frequently during transfers. The high loads during ADL tasks might be a risk factor for overuse of the upper-extremity joint, which would be in line with epidemiologic data.…”
Section: Methodsmentioning
confidence: 99%
“…There is also the absence of sufficient recovery time: subjects must perform lifts during the day and propel themselves. Tasks like making a transfer are performed around 15 times a day, 1 and, as shown by Janssen et al, 32 a physical strain of 60% of the heart rate reserve occurs frequently during transfers. The high loads during ADL tasks might be a risk factor for overuse of the upper-extremity joint, which would be in line with epidemiologic data.…”
Section: Methodsmentioning
confidence: 99%
“…However, activities such as transferring and wheeling do require activation of major muscle groups and as a result can be very strenuous. 9,10 The increased strain accompanying these ADL may deter participation and consequently limit opportunities for community integration. However, it has been demonstrated that increased fitness reduces the strain of ADL.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been demonstrated that increased fitness reduces the strain of ADL. 9 Accordingly, increasing fitness may allow individuals with SCI to complete strenuous ADL (for example, mobility activities) with less difficulty and for prolonged periods. Moreover, with increased fitness individuals may become more proficient at performing passive ADL (for example, personal care activities) and require less time to complete this type of activity.…”
Section: Introductionmentioning
confidence: 99%
“…In persons with a spinal cord injury (SCI), HR has also been used to prescribe training intensity, 1 as well as to indicate physical strain in daily activities. [2][3][4] The guidelines of the American College of Sports Medicine (ACSM) for training of able-bodied persons -50-85% heart rate reserve (HRR) 5 -have also been applied in training studies with persons with paraplegia (PP) 6 as well as tetraplegia (TP). 7,8 These guidelines may be valid for persons with PP, as several studies [9][10][11][12][13][14] showed a strong individual linear HR-VO 2 relationship in persons with PP.…”
Section: Introductionmentioning
confidence: 99%